2015
DOI: 10.1016/j.bbmt.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stromal Cells from Patients with Acute and Chronic Graft-versus-Host Disease Deploy Normal Phenotype, Differentiation Plasticity, and Immune-Suppressive Activity

Abstract: The success of allogeneic hematopoietic stem cell transplantation (allo-HSCT) is often limited by the development of acute and/or chronic graft-versus-host disease (GVHD). The lack of effective therapies to treat steroid-refractory GVHD patients has bolstered clinical evaluation of mesenchymal stromal cell (MSC) therapy for GVHD. Currently, testing of MSCs for the treatment of GVHD has exclusively used allogeneic MSCs despite emerging evidence that MSCs lose their immunoprivileged status in vivo. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…However, the cytogenetic stability of MSCs following viral transduction needs to be established to the allay safety issues of malignant transformation. The nucleofection technology is a safe non-viral electroporation-based transfection system (24,25). In this study, we modified ADSCs with the plasmid pcDNA3.1 that can expressed the OX40Ig fusion protein in eukaryotic expressiion systems by nucleofection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytogenetic stability of MSCs following viral transduction needs to be established to the allay safety issues of malignant transformation. The nucleofection technology is a safe non-viral electroporation-based transfection system (24,25). In this study, we modified ADSCs with the plasmid pcDNA3.1 that can expressed the OX40Ig fusion protein in eukaryotic expressiion systems by nucleofection.…”
Section: Discussionmentioning
confidence: 99%
“…Patients enrolled in this study had active GvHD or inflammatory bowel disease at the time of bone marrow harvest, as described previously (Copland et al, 2015; Dhere et al, 2016). Bone marrow aspirates were subjected to a Ficoll density gradient to obtain mononuclear cells, as described previously (Chinnadurai et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Another significant challenge facing development of MSC-based therapies is the lack of well-defined, robust assays for assessing their immunosuppressive function. Current assays for assessing MSC immunosuppressive capacity exist; however, they often rely on quantification of only a few markers in a single culture condition (8,9,20). Based on these limitations, we developed a robust, quantitative method of assessing the immunosuppressive capacity of human bone marrow-derived MSCs and further demonstrated that morphological features of IFN-γ-stimulated MSCs can be used to predict their overall immunosuppressive capacity.…”
Section: Morphological Features Of Mscs After Ifn-γ Stimulation Corrementioning
confidence: 99%
“…A major challenge in the development of consistently effective MSC-based immunosuppressive therapies is that MSC lines derived from different donors and manufacturing processes (i.e., cell expansion) can possess markedly dissimilar immunosuppressive function (3,5,6). Although methods exist to assess MSC immunosuppression in vitro, they are often based on only a few measured outcomes, assay culture conditions, and donor MSC samples (5,(7)(8)(9). To improve upon these methods, we developed an experimental and analytical approach to quantify MSC-mediated immune suppression using principal-component analysis (PCA) to integrate multiple measurements of T-cell activation assessed at a range of MSC densities.…”
mentioning
confidence: 99%